2020
DOI: 10.1088/2043-6254/ab790f
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal applications for nano-additives synthesized with a bio-based approach

Abstract: Filamentous fungi are microorganisms that cause deterioration of structural materials due to their ecological plasticity and vegetative functions. Functionalised sol-gel based products can be used to control this kind of biodeterioration through the association to antifungal active additives which are trapped in the siloxane crosslinking. Bioactive additives and materials to control microbial growth have been gaining more attention over the years. However, due to the concern about their toxicity, bio-based app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Then, it is necessary to protect the monuments from where the species were isolated. This protection can be performed through the application of antifungal coatings on the materials in order to control the fungal deterioration [43].…”
Section: Exposure Studies In Humidity Chambermentioning
confidence: 99%
“…Then, it is necessary to protect the monuments from where the species were isolated. This protection can be performed through the application of antifungal coatings on the materials in order to control the fungal deterioration [43].…”
Section: Exposure Studies In Humidity Chambermentioning
confidence: 99%
“…Although a variety of other synthetic approaches have also been used, including the use of microorganisms, so-called biosynthesis (8%), used for ZnO, 49 Cu NPs, 50 and Ag NPs. 16,51 Electrochemical methods (4%) have also been used to prepare ZnO 19 and Cu NPs, 52 and sonochemical methods (4%) are currently trending as a convenient, rapid, and cost-effective route to obtain NPs such as ZnO. 53,54 Physical vapor deposition has also been used for the synthesis of In-doped ZnO.…”
Section: Synthesis and Properties Of The Nanomaterials Tested As Biocides In Heritagementioning
confidence: 99%
“…Furthermore, the use of copper materials on membrane systems (i.e., reverse osmosis membranes) or in dental care procedures has also been explored by the scientific community, however, at a lower extent (5% and 7% of the manuscripts works). The remaining 7% of original studies were related with the petrochemical industry (1.7%) [ 45 ], construction sector–bricks (1.7%) [ 46 ], food contacting surfaces (1.7%) [ 47 ] and space flight materials (1.7%) [ 48 ].…”
Section: Copper Surfaces On Biofilm Prevention and Controlmentioning
confidence: 99%
“…Copper is a widely used material due to its interesting workability characteristics and corrosion resistance. In addition to the applications described above, the antibacterial and antibiofilm properties of copper are relevant for many other applications such as in the food industry [ 121 ], fuel and oil facilities [ 45 ], construction sector [ 46 ] or even in space flight or space station equipment [ 48 ]. Dygico, et al [ 122 ] tested different materials that can be found in the mushroom production environment such as SS, aluminum, rubber, polypropylene, polycarbonate, concrete, borosilicate glass and copper and found that the use of copper reduced significantly the number of culturable Listeria monocytogens adhered on the surface [ 122 ].…”
Section: Other Applications For Copper Surfacesmentioning
confidence: 99%
See 1 more Smart Citation